Kemmerer's Modern Currency Reforms - Willis, H. Parker; Kemmerer, Edwin (Quarterly Journal of Economics, 1917)
Journal Article Kemmerer's Modern Currency Reforms Get access H. Parker Willis H. Parker Willis Federal Reserve Board, Washington, D. C. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 31, Issue 3, May 1917, Pages 530–536, https://doi.org/10.2307/1883387 Published: 01 May 1917